(untitled) (Islamic Sciences Journal, 2026)
Surah At-Tahrim represents a unique model of family and educational guidance, as it addresses an issue related to the sanctity of the Prophet’s household and the disclosure of secrets. It presents an integrated set of methods of guidance and discipline for women, ranging between gentleness and firmness, encouragement and warning, and grounded in the principle of both individual and collective responsibility. This approach is exemplified in the manner of dealing with the wives of the Prophet (peace be upon him). It is based on implicit and indirect reproach, where blame is not directed at the wives explicitly; rather, the discourse begins with the verse: “O Prophet, why do you prohibit what Allah has made lawful for you, seeking the pleasure of your wives?” This method causes the wives to sense the mistake through reproaching the other party, an approach intended to preserve dignity and save face for those being admonished. Another method is overlooking details (educational discretion), as refraining from mentioning certain mistakes reflects a Prophetic etiquette in handling marital and familial errors. However, when the mistake affected the status of Prophethood and the exemplary role it represents, the tone shifted to strong warning and severe admonition,